The nature of fixed language in the subtitling of a documentary film - Martins, Cláudia (2011)
This research is based on the assumption that audiovisual translation (AVT ) performs a social and cultural function over its viewers, thus still justifying studies that focus on linguistic issues. This is particularly striking for the reading literacy in countries such as Portugal, that are traditionally subtitling countries, even if dubbing and voice-over are also occasionally used, particularly in the case of documentaries. The purpose for this research is to analyze the examples of restricted lexical occurrence, i.e. set phrases or semantic phrasemes (Mel’čuk 1995), depending on the terminology chosen, within the two versions of the AVT – subtitling and voice-over – of a documentary film called “The Real Da Vinci Code”. In order to achieve this purpose, we chose to follow a case study methodology that allowed us to center our attention on and single out a specific feature of language – set phrases – used in this type of audiovisual texts – documentary films.